Changes in proteins, physical stability and structure in directly heated UHT milk during storage at different temperatures. (August 2017) - Malmgren, Bozena; Ardö, Ylva; Langton, Maud; Altskär, Annika; Bremer, Maria G.E.G.; Dejmek, Petr; Paulsson, Marie
Abstract: Changes occurring in directly heated UHT milk were studied during storage at 5, 22, 30 and 40 °C. Industrially produced UHT milk samples were analysed for changes in enzymatic activity, protein modification, destabilisation of casein micelles and relocation of milk proteins in relation to sedimentation and gel formation. Sedimentation occurred at all temperatures, and the protein composition of the sediments reflected the composition of its liquid phase; however, there was no α-lactalbumin, β-lactoglobulin or κ-casein present in sediments. Tendrils composed of β-lactoglobulin and κ-casein were seen on casein micelles after UHT treatment and grew in length prior to gelation. High degrees of lactosylation of proteins and peptides were clearly correlated with the absence of gelation and long tendrils. Gelled samples showed complete hydrolysis of intact β-casein, and limited lactosylation of β-lactoglobulin and κ-casein.